Collaborative Tagging Supported Knowledge Discovery - Zauder, Krešimir; Lasić-Lazić, Jadranka; Banek Zorica, Mihaela (2007)
Web 2.0 has brought about a new sort of user centred services which rely a great deal on flexible organizational capabilities designed for user-supplied organization. Collaborative tagging is especially interesting in this context and this article explores what this kind of organization in connection with some Web 2.0 principles means for knowledge discovery in various ways. To fully explore this, the article defines collaborative tagging and gives an overview of collaborative tagging in general, of services using it and of tags themselves. It concludes with mechanisms this kind of approach to knowledge organization provides for knowledge discovery.
Projekt MZOS
ENG